Phytohaemagglutinin as a modelator of DNA repair measured by chromosome aberration analysis in micronucleus assay in ionizing radiation biodosimetry - Đurinec, Martina (Radiology and oncology (Ljubljana), 2006)
Background. There are some correlations between cell's ability to remove DNA damage and proliferative activity. The aim of this study was to examine the influeace of phytohaemagglutinin (PHA) on DNA repair capacity in isolated human lymphocytes exposed to ionizing radiation. Methods. Lymphocytes were isolated from the whole blood using a Ficoll centrifugation. As the source of y-rays 60 Co source Alcon, CGR-MeV was used. To achieve the absorbed dose of 2Gy a total exposure to radiation lasted for 1.24 minutes at room temperature.Possible differences in DNA repair efficiency were monitored by chromosomal aberration analysis and rnicronucleus assay, 48 and 72 h after thePHA stimulation, respectively. Results. The number of dicentric chromosomesand acentric fragments were significantly increased in lymphocytes stimulated by phytohaemagglutinin immediately after the irradiation compared to the cultures where the activator was added after 1, 2 and 4 h. The micronucleus assay did not show any significant differences in the number and distribution of micronuclei regardless of the time when the mitogen activator was added. Conclusions. The observed non-significat decreases in the total number of chromosomal aberration and micronuclei suggest that phytohaemagglutinin does not significantly contribute to the DNA repair.
Keywords: celice; Chromosome Aberrations; DNA; DNA Damage; DNA Repair; DNA, obnova; DNA, poškodba; Drug Effects; Fitohemaglutinini; kromosomi; Kromosomske aberacije; Limfociti; Lymphocytes; Micronucleus Tests; Mikronukleusni testi; obsevanje; Phytohemagglutinins; poškodbe; Radiation Effects; Radiation, Ionizing; Sevanje ionizirajoče